A Survey Report of Disease Fields of District; Swabi, Buner, Haripur and Mardan Province of Khyber Pakhtunkhwa: A Survey Report of Crop Losses (Biological Sciences - PJSIR, 2021)
A survey of diseased fields of total (35) areas located in four different Districts of Khyber  Pakhtun Khwa like Buner (4 areas), Swabi (23 areas) Mardan (3 areas) and Haripur (5areas) was carried out for estimation of losses and identification of root disease causing pathogens in 14 different economically important crops like Tobacco (Nicotiana tabacum), Ladyfinger (Abelmoscus esculentus), Chilli (Capsicum anuum), Eggplant (Solanum melongena), Maize (Zea mays), Tomato (Solanum lycopersicum), Wheat (Triticum estivum), Garlic (Allium sativum), Mustard (Brassica compestres), Clover (Trifolium repens), Onion (Allium cepa), Turnip (Brassica rapa), Radish (Raphanus sativus) and Pea (Pisum sativum). The most common root rot pathogens found in all the areas visited were Alternaria alternate, A.solani, Rhizoctonia solani Macrophomina phaseolina and species of Fusarium viz., Fusarium solani and F.oxysporum. Two species of root-knot nematode Meloidogyne javanica and M. incognita were also found causing root- knot disease. The eggplant was found upto 20-76% losses when an infection caused by the combined effect of F. oxysporum, M.phaseolina. R. solani and root-knot nematodes. Similarly, the loss of chiliplants was found 40-65% due to the combined effect of F. solani, M.phaseolina, R. solani, and root-knot nematodes. Zea mays crops were reported 50-77% losses due to Drecslera spp, F.solani, and A. solani Losses recorded by these root-rot and root-knot pathogens were found variable depending upon a combination of pathogens, temperature and soil types.